2014
DOI: 10.13189/ujph.2014.020102
|View full text |Cite
|
Sign up to set email alerts
|

Benefits from Increasing Salary, Employee Benefits and Rank for Promotion the Nursing Shortage in Macao Chinese Society

Abstract: The purpose of this study was to compare and discuss the modified policy for nursing staff in the public sector in Macao Chinese society. This study compared the past and present modifications in the bill of the Rank and Grade System in the public sector. The greatest concerns of the nursing staff included the old bill of rights, the grading system for the nursing staff, which needed to be modified, and improvements, especially with regard to salary, employee benefits and rank for promotion. The essential elem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…This caused a substantial increase in salary, employment benefits, on-shift allowances, and promotion opportunities (C. S. U. Leong, 2014). This study found that the average salary of a nurse is much higher than that of the general population in Macao.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…This caused a substantial increase in salary, employment benefits, on-shift allowances, and promotion opportunities (C. S. U. Leong, 2014). This study found that the average salary of a nurse is much higher than that of the general population in Macao.…”
Section: Introductionmentioning
confidence: 79%
“…On the positive side, the Macao government has favorably updated the employment contract for nurses working in public sectors in the past decades. This caused a substantial increase in salary, employment benefits, on-shift allowances, and promotion opportunities (C. S. U. Leong, 2014).…”
Section: Introductionmentioning
confidence: 99%